Optimizing the Maintenance of City Parks by the Public Works and Spatial Planning Office of the City of Sukabumi - Amirulloh, M. Rijal; Sani, Faisal; Fadhilah, Ahmad; Ambarwati, Bunga Ayu; Kamal, Syifa Nurfauziah (Jurnal Manajemen Pelayanan Publik, 2026)
Rapid urban growth creates major challenges in city park management. This study aimed to: (1) evaluate current maintenance effectiveness at Sukabumi City parks, (2) identify key operational constraints, and (3) develop improvement recommendations. By applying a qualitative approach with Siringoringo’s optimization framework, data were collected through observations, interviews, and documentation with officials from the Parks Section. Results indicated a maintenance effectiveness of 88-92%, yet the organization faced significant challenges: a staff deficit (24 officers for extensive coverage), outdated equipment (a skylift from 2003), and a limited budget (approximately 600-800 million rupiah annually). Current strategies include specialized staff training, easy-to-maintain plants, and diverse funding sources through Corporate Social Responsibility partnerships. The study recommends comprehensive improvements, such as hiring more staff, equipment modernization, and standardized procedures to achieve optimal city park management. The positive correlation between budget allocation and maintenance effectiveness confirms the importance of adequate resource distribution for sustainable urban parks.